Organoleptic Quality of Beef Meatballs Using Chicken Giblets - Hafid, Harapin; Owen Afriansyah; Nur Santy Asminaya (Jurnal Peternakan Integratif, 2023)
Meat is a food of animal origin that has high nutritional value, because meat contains several nutrients including protein, fat, minerals and vitamins. This study aims to determine the physical and organoleptic quality of beef meatballs using giblets. The materials used in this study were beef, giblets, tapioca flour, garlic, salt, flavourings, and ice cubes. This study used a completely randomized design consisting of 4 treatments and 4 replications P0 (100%) beef without giblets, P1 (80%) beef + 20% liver, P2 (80%) beef + 20% gizzard, P3 ( 80) beef + 20% heart. The parameters measured in this study were pH, cooking loss, yield, shape, aroma, color, texture, taste, elasticity and general acceptance. The results of this study indicate that the addition of giblets to chicken meatballs. beef meatballs. However, it did not have a significant effect (P>0.05) on the organoleptic test of beef meatballs, especially on the variables of shape, aroma, texture, taste, and general acceptance